Papers and proceedings of a conference sponsored by the Library Association and the Royal Statistical Society and held on 5th July, 1965 - Mallaber, Kenneth Aldridge; Library Association; Royal Statistical Society (Great Britain) (London : Library Association, 1966)
This volume comprise of papers and proceedings of a conference sponsored by the Library Association and the Royal Statistical Society and held on 5th July, 1965. The purpose was to examine how best to organise libraries to serve the real needs of users and potential users.
lje 22/1/19
Loans
Keywords: Special libraries; Library services